Effect of 5?aminolevulinic Acid on PLB Culture of Cymbidium dayanum In Vitro (Plant Tissue Culture and Biotechnology, 2015)
Abstract not availablePlant Tissue Cult. & Biotech. 25(1): 99-102, 2015 (June)